Eye lens diameter and weight as an age indicator in Rhynchorhamphus georgi (Valenciennes, 1846)(family: Hemiramphidae) collected from the sea of Oman - J. Al-Mamry; L. A. Jawad; M. Al-Yarubi; Al-Mamari, H.; E. Al-Rassady (ՀՀ ԳԱԱ հրատ.)
Specimens of Rhynchorhamphus georgi have been collected from waters around Muscat City at the coasts of the Sea of Oman. The ocular lens diameter and weight were tested as an additional age indicator to those already in use. The results showed that the diameter of the eye lens can be used for identifying first-year animals, while the eye lens weight proved unreliable for age determination. Rhynchorhamphus georgi նմուշները ընտրվել էին Օմանի ծովի ափամերձ՝ Մուսկաթ Սիթին շրջապատող ջրերից: Աչքի ոսպնյակի տրամագիծն ու քաշը հետազոտվել են որպես աճի լրացուցիչ ցուցանիշ: Արդյունքները ցույց են տալիս, որ աչքի ոսպնյակի տրամագիծը կարող է օգտագործվել բացահայտելու մեկ տարեկան կենդանիներին, մինչդեռ աչքի ոսպնյակի քաշը կենդանիների տարիքը չի որոշում: Образцы Rhynchorhamphus georgi были отобраны из вод вокруг Сити Мускат у побережья моря Оман. Диаметр и масса линзы окуляра были исследованы в качестве дополнительного возрастного показателя. Результаты показали, что диаметр глазной линзы может быть использован для выявления годовалых животных, между тем масса глазной линзы не определяет возраста животного.
Keywords: Biology; Zoology